2004
DOI: 10.1029/2003gb002183
|View full text |Cite
|
Sign up to set email alerts
|

Modeling estimates of the global emission of dimethylsulfide under enhanced greenhouse conditions

Abstract: [1] We have used a marine food-web model, an atmosphere-ocean general circulation model (GCM), and an empirical dimethylsulfide (DMS) algorithm to predict the DMS seawater concentration and the DMS sea-to-air flux in 10°latitude bands from 70°N to 70°S under contemporary and enhanced greenhouse conditions. The DMS empirical algorithm utilizes the food-web model predictions of surface chlorophyll and the GCM's simulation of oceanic mixed layer depth. The food-web model was first calibrated to contemporary clima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
85
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 85 publications
(116 reference statements)
2
85
5
Order By: Relevance
“…The effect of anthropogenic climate change on DMS production and emission has been shown to be relatively small globally (Bopp et al, 2003;Gabric et al, 2004;Gunson et al, 2006;Vallina et al, 2007;Kloster et al, 2007), although, regionally, larger sensitivities have been reported (Bopp et al, 2003;Kloster et al, 2007). Most of these studies predict an increase in global surface DMS concentrations or sea-air fluxes of about 2 to 14 % in response to global warming, while Kloster et al (2007) model a 10 % decrease under a future scenario.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of anthropogenic climate change on DMS production and emission has been shown to be relatively small globally (Bopp et al, 2003;Gabric et al, 2004;Gunson et al, 2006;Vallina et al, 2007;Kloster et al, 2007), although, regionally, larger sensitivities have been reported (Bopp et al, 2003;Kloster et al, 2007). Most of these studies predict an increase in global surface DMS concentrations or sea-air fluxes of about 2 to 14 % in response to global warming, while Kloster et al (2007) model a 10 % decrease under a future scenario.…”
Section: Introductionmentioning
confidence: 99%
“…C 6 H + 6 in the presence of benzene). In pure nitrogen or air, trace water vapor leads to the formation of water clusters, H + (H 2 O) n , as the dominant positive ion species (Good et al, 1970). Trace gas constituents with lower ionization potential or higher proton affinity than the dominant ions are ionized by charge or proton transfer.…”
Section: Historical Developmentmentioning
confidence: 99%
“…On the subsequent DYCOMS-II field program, DMS flux measurements by APIMS-ILS were used to compute entrainment velocities at the cloud-top inversion of a stratocumulus-capped marine boundary layer (Stevens et al, 2003;Faloona et al, 2005). Good et al (1970) established the sequence and kinetics of ion formation in moist nitrogen at 4 Torr, leading from the initial ionized species, N + 2 , to water clusters of the following form, where the distribution of clusters up to H + (H 2 O) n depends on water vapor concentration, pressure and temperature.…”
Section: Historical Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Modelling by Lovelock and Kump [82] indicated that the sulfur cycle could exert its greatest influence over climate during glacial periods and in the absence of an anthropogenic influence. Gabric et al [83] also used modelling to understand the DMS production in surface waters and then extended this work to assess the response of marine biology to a changing climate, [84,85] showing the expected increase in wind speed would enhance DMS fluxes to atmosphere. [86] More recent modelling studies [87][88][89] suggest that climate change will result in a small, 1-2%, global increase in DMS emissions, with the potential for a small negative feedback (cooling).…”
Section: Feedbacksmentioning
confidence: 99%